The Influence of Board of Commissioners Size, Board of Directors Size, and Audit Committee on the Valuation of Companies in the Technology Sector Listed on the Indonesia Stock Exchange (BEI) - Tamba, Rani; Safitri, Tsamara; Panjaitan, Gloria; Athaya, Nada; Azzahra, An (Indonesian Journal Publisher, 2025)
The swift growth of Indonesia’s technology industry demands that companies not only lead in innovation but also adopt strong corporate governance practices to ensure long-term value creation. This research seeks to empirically analyze the impact of corporate governance structure—which includes the size of the Board of Commissioners, the size of the Board of Directors, and the presence of an Audit Committee—on firm value within the technology sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Employing a quantitative method with multiple regression analysis, the study utilizes data derived from the annual reports of companies selected through purposive sampling. Firm value is assessed using the Price to Book Value (PBV) as the primary indicator. The findings reveal that, individually, the sizes of both the Board of Commissioners and the Board of Directors do not significantly affect firm value. However, the presence and active involvement of an Audit Committee positively and significantly influence firm value. When considered collectively, the three governance variables exert a significant impact on firm value. These results suggest that effective corporate governance depends not merely on the number of supervisory roles but more on the quality and collaboration among governance components, which enhance transparency, accountability, and investor trust. This study offers valuable insights for corporate management, investors, and regulators in improving governance frameworks.